Unlocking the Potential of Contract Farming: Lessons from Ghana - Kudadjie-Freeman, C.; DeBruin; Hockzona, M.; Hughes, S.G.; Richards, P.; Offei, S.K.; Struik, P.C. (The Gatekeeper Series, IIED 139 (3): 2-14, 2008)
There has been many reviews and evaluation of contract farming and its usefulness for the small farmer in Africa. Some see contractual arrangements as disadvantageous to farmers, while others see them as beneficial- Despite these debates, contract farming is to likely to continue as a means of keeping small farmers involved in markets. It is therefore important to learn from past experiences in order to improve the working of the system as a whole. This paper analyses sorghum contract farming in north-east Ghana in order to explore ways of making such arrangements viable for small farmers. The analysis draws on the convergence of sciences approach, which sees both science and social relation interactions among the relevant stakeholders as important for developing small farmer-related agricultural innovations (technology, procedures, new forms of organization). The study reveals that the failure and problem encountered in this particular contracting scheme were both technical and institutional. The technical issues were a combination of pest problems, the environment and the sorghum variety chosen. The institutional issues involved the contractual arrangements and relations between the contracting parties. The authors argue that if contracts are to be fair, they must allow for compensation, contingencies and production risks. But scientific knowledge is required in order to adequately incorporate these elements. The authors suggest technological and institutional changes to improve contract farming. Science is needed to tackle specific technical problems likely to be faced by farmers, these should then become a basis for negotiating beneficial contract terms for all parties. They also suggest that while farmers could improve their negotiation power by forming organisations, governments should also strengthen the institutional and legal framework process for small farmers, who are often the weaker of the contracting parties.
Keywords: Contract-farming; Ghana; Technology Development; Sorghum; Stakeholders